2003
DOI: 10.1074/jbc.m300632200
|View full text |Cite
|
Sign up to set email alerts
|

Redox-regulated Rotational Coupling of Receptor Protein-tyrosine Phosphatase α Dimers

Abstract: Receptor protein-tyrosine phosphatase ␣ (RPTP␣) constitutively forms dimers in the membrane, and activity studies with forced dimer mutants of RPTP␣ revealed that rotational coupling of the dimer defines its activity. The hemagglutinin (HA) tag of wild type RPTP␣ and of constitutively dimeric, active RPTP␣-F135C with a disulfide bond in the extracellular domain was not accessible for antibody, whereas the HA tag of constitutively dimeric, inactive RPTP␣-P137C was. All three proteins were expressed on the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 39 publications
2
48
0
2
Order By: Relevance
“…Mutation of Cys 723 renders full-length RPTP␣ at least in part insensitive to oxidation, in that H 2 O 2 treatment or UV treatment of living cells completely inactivates wild type RPTP␣, but not RPTP␣-C723S (8,28). H 2 O 2 -induced inactivation of RPTP␣ is due to a conformational change in RPTP␣-D2, which leads to stabilization of an inactive RPTP␣ dimer conformation (8,29). How RPTP␣-D2 changes conformation in response to H 2 O 2 remains elusive and will require elucidation of the crystal structure of oxidized RPTP␣-D2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation of Cys 723 renders full-length RPTP␣ at least in part insensitive to oxidation, in that H 2 O 2 treatment or UV treatment of living cells completely inactivates wild type RPTP␣, but not RPTP␣-C723S (8,28). H 2 O 2 -induced inactivation of RPTP␣ is due to a conformational change in RPTP␣-D2, which leads to stabilization of an inactive RPTP␣ dimer conformation (8,29). How RPTP␣-D2 changes conformation in response to H 2 O 2 remains elusive and will require elucidation of the crystal structure of oxidized RPTP␣-D2.…”
Section: Discussionmentioning
confidence: 99%
“…response to H 2 O 2 treatment, because RPTP␣-D2 undergoes a conformational change in response to oxidation, leading to stabilization of an inactive dimeric conformation (8,29). Mutation of the catalytic cysteine in RPTP␣-D2 renders RPTP␣ less sensitive to oxidation, in that H 2 O 2 and UV treatment of living cells do not lead to complete inactivation of RPTP␣-C723S, whereas wild type RPTP␣ is inactivated completely (8,28).…”
mentioning
confidence: 99%
“…Recently, by using a conformation-sensitive antibody method, we found that H 2 O 2 treatment leads to a change in rotational coupling of the RPTP␣ dimers that is dependent on the catalytic Cys-723 of the membrane-distal PTP domain (27). The conformation of untreated RPTP␣ dimers is similar to the conformation of the active constitutive dimer mutant RPTP␣-F135C, whereas the H 2 O 2 -treated RPTP␣ dimers adopt the conformation as found with an inactive constitutive dimer mutant, RPTP␣-P137C.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that LAR-D2, like RPTP␣-D2, shows a conformational change upon oxidative stress (21). Like HA-RPTP␣ (27), HA-ED␣-LAR shows a change in rotational coupling of the dimer upon H 2 O 2 treatment as detected by the accessibility of the HA tag on living cells transfected with HA-ED␣-LAR (Fig. 5A).…”
Section: Rapid Formation Of Intermolecular Disulfide Bonds Between Rpmentioning
confidence: 93%
See 1 more Smart Citation